THE PHENOMENON OF ONTOLOGICAL GUILT, METAPHYSICAL RESPONSIBILITY, AND PSYCHOLOGICAL DRAMATIC TENTION IN “I AM GUILTY” BY ALEKSANDR FAYNBERG - Odilova Charosxon Shavkatjon kizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Annotation: This article examines the phenomenon of ontological and metaphysical guilt in the poem “I Am Guilty” by Aleksandr Faynberg through philosophical and psychological frameworks. The study analyzes the lyrical subject’s confession of universal guilt as an expression of existential responsibility, ecological awareness, historical accountability, and theological paradox. Drawing upon the ideas of Martin Heidegger, Jean-Paul Sartre, Karl Jaspers, Hannah Arendt, Sigmund Freud, and Viktor Frankl, the article interprets guilt not as a purely moral or legal category but as an ontological condition of human existence. The research demonstrates that the poem constructs a model of global responsibility in which individual innocence coexists with collective accountability. Philosophical and psychological interpretations are presented as complementary dimensions that reveal the depth of the poem’s ethical, existential, and metaphysical discourse.